AoI-enabled multi-node cooperative sensing based on integration of sensing, communication, and computing in vehicular networks - Yiqing ZHOU; Haoyue ZHANG; Yanli QI; Qing CAI; Ling LIU; Jiangzhou WANG (Tongxin xuebao)
For the requirements of real-time services in autonomous driving systems, such as high-definition (HD) maps, based on the integration of sensing, communication, and computing, a multi-node cooperative sensing mechanism was proposed with the age of information (AoI) as the real-time indicator.Considering the constraints on communication and computing resources and vehicle energy consumption, the information collection, transmission and processing of sensing nodes were optimally scheduled to minimize the AoI averaged over time.A Lyapunov-based online scheduling algorithm was proposed to transform the long-term stochastic optimization problem into an online optimization problem, which could be solved with low complexity.Compared with the existing mechanism considering integrated communication and computing, the proposed mechanism can improve real-time performance by 9%～50%.